Political Idealism in Poland During the Crisis of 1980-1981 - Gluchowski, Leszek (My University, 1986)
Despite the complexity of the Polish August, political idealism stands out as the most pervasive and pressing influence on Polish society during that period. Moreover, the Polish crisis fits a pattern in Polish history which has been dominant since the 18th century. Ever since the partitions, the Poles have had to make certain assumptions about their political dilemma. The focal point of the political debate in Poland has centred on combating foreign oppression. Therefore, the great divide in Polish political thought has characteristically been between two opposing schools of thought. On the one side, the political idealists, or the "romantics", as the Poles call them. On the other side, the political realists, or the "positivists". This division cuts through various social and political groupings and tends to split the Poles between those who advocate independence as a first priority and those who advocate organic work. Because of the pivotal role played by these two competing forces in Polish history, they have been able to bring into their ranks the different political groups with varied ideologies that have existed in Poland over time. While Poland, like other nations, has been divided on internal social reform, the division between the idealists and realists is still the most dominant feature of Polish politics. The dynamics of the competition between the realists and idealists has produced a characteristic cyclical rhythm in Polish politics, where one of the two groups would gain the confidence of the Polish people and then, for some reason, lose it to the other. By the end of 1981, and especially after the Solidarity Congress in October, political idealism had become the guiding force. The Poles were unwilling to moderate both their desire for extensive economic and political reforms and their historical dream of Polish independence.
Keywords: Political Science; Political Science